Palliative and end‐of‐life care in pediatric solid organ transplantation. (25th November 2014) - Fowler, Amy; Freiberger, Dawn; Moonan, Marilyn
Abstract End‐of‐life care is a component of palliative care and takes a holistic, individualized approach to patients, focusing on the assessment of quality of life and its maintenance until the end of life, and beyond, for the patient's family. Transplant teams do not always make timely referrals to palliative care teams due to various clinician and perceived family barriers, an important one being the simultaneous, active care plan each patient would have alongside an end‐of‐life plan. Application of findings and further research specific to the pediatric solid organ population would be of significant benefit to guide transplant teams as to the most effective time to introduce end‐of‐life care, who to involve in ongoing discussions, and important ethical and cultural considerations to include in care planning. Attention must also be paid to clinician training and support in this challenging area of health care.